EARLY FEMINIST CONSCIOUSNESS AND IDEA AMONG MUSLIM WOMEN IN 1920s INDONESIA - Farid Muttaqin (Jurnal Ilmiah Peuradeun, 2015)
Colonial encounters were pivotal in the development of feminist consciousness and the women’s liberation movement among women and men in colonized countries like Indonesia. However, the influences of the colonial encounter on the foundation of feminist consciousness were not developed by passive recipients of colonial ideas. The initial idea of Islamic education for Muslim girls showed the crucial influence and contribution of Islam and Muslim women to early feminist ideas in Indonesia. Islamic education for Muslim girls was intended to answer the specific problem of women’s lack of empowerment within family and social life. The idea of education for women’s empowerment transformed into part of the nationalist movement against colonialism when in the end it led to the foundation of Muslim women’s organizations that brought Islam as a critical tool. Foundation of Muslim women’s organizations was a critical internal effort against patriarchal values and structures in the Islamic context. I argue that these feminist agendas, such as Islamic education for girls and Muslim women’s organizations, were integral to the Islamic reform movement.